Consider this hypothetical reaction: A + 2B + C ---> AB2C Experimental evidence shows that the reaction occurs in three elementary steps?
Step 1: A + B ---> AB (slow)
Step 2: AB + B ---> AB2 (fast)
Step 3: AB2 + C <---> AB2C (fast, reversible)
(See graphic: http://i270.photobucket.com/albums/jj83/metro_cub/RateMech_zps4d0e5f9d.jpg)
Which rate law is consistent with this mechanism?
(A) rate = k[A][B]
(B) rate = k[AB][B]
(C) rate = k[AB][AB2]
(D) rate = k[A][B]^2[C]
Please explain how you got the answer. Thank you :-)